Homosexualities and Citizenships in Colombia - Aparicio Erazo, Jorge Luis (2009)
This article attempts to analyze the ways in which gays people can access the exercise of citizenship in Colombia. It is argued that citizen participation of homosexuals doesn’t depend nor is exhausted by the political and normative dimension, but that it goes hand in hand with individual, informal and micropolitical processes; as well as negotiations between the two areas. From this perspective, the actions realized by the formal activist groups, as well as a series of everyday actions and informal associations (that are transformed into mechanisms of integration or subjective alienation of homosexuals in society) gain importance.